2021
DOI: 10.1088/1742-6596/1763/1/012090
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of DSSC with PEDOT carrageenan as electrolyte system

Abstract: This study aims to produce DSSC solar cells using PEDOT as a substitute for iodine. This experiment was carried out in the physics laboratory of the Tadulako University FKIP. TiO2 was deposited on FTO glass measuring 2.5 x 2.8 cm using the doctor blade method. TiO2 film was produced after heating in a furnace at 450 ☐C. Subsequently, the film was soaked in Routinized dye for 30 minutes. PEDOT Carrageenan Lambda 1:1 is then dripped on a TiO2/dye layer and covered with a platinum counter electrode. The results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…In other studies, PEDOT:Carrageenan was synthesized using λ-carrageenan with a ratio of 1:1 [ 49 ] and κ-carrageenan with a ratio of 1:2 [ 50 ] in weight percent (wt%). Both showed low performance of DSSC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies, PEDOT:Carrageenan was synthesized using λ-carrageenan with a ratio of 1:1 [ 49 ] and κ-carrageenan with a ratio of 1:2 [ 50 ] in weight percent (wt%). Both showed low performance of DSSC.…”
Section: Resultsmentioning
confidence: 99%
“…Both showed low performance of DSSC. It was caused by the rigidity of PEDOT chain; electron transport was not as efficient as compared to the liquid system [ 49 , 50 ]. Both studies have synthesized the PEDOT:Carrageenan with a similar process via in-situ polymerization by mixing EDOT monomer and carrageenan solution.…”
Section: Resultsmentioning
confidence: 99%
“…Fluorine-doped Tin Oxide glass is a type n semiconductor that is transparent and conductive. The spray pyrolysis method carried out by researchers to produce FTO glass in this study can be seen at the following link: https://www.youtube.com/watch?v=e1gEl-aC478 (Palamba et al, 2021). The FTO glass produced through the sintering and ionization processes in this experiment can be seen in Figure 2.…”
Section: Fto Glass Fabrication With Spray Pyrolysis Methodsmentioning
confidence: 99%
“…A few of the experimental activities carried out in making FTO glass and making DSSC solar cells in this study have been documented in video and have been uploaded online so that students can watch them (Palamba et al, 2021). This is expected to help support laboratory-based learning on some relevant physics materials such as Ohm's Law, X-ray Diffraction, Efficiency, and Electric Power.…”
Section: Application Of Fto In Dye-sensitized Solar Cells (Dssc)mentioning
confidence: 99%
“… 21,22 Until now, polysaccharides and modified polysaccharides based materials were in reality for their superior ionic conductivity at room temperature, which includes, for example, chitosan, 23,24 cellulose 25 and carrageenan. 26 Recently, Di Noto et al reported another two main kinds of hybrid inorganic–organic PEs that are mono-phase and multi-phase PEs. 27 Also, various inorganic filler were also reported, such as titania (TiO 2 ), zircronia (ZrO 2 ), carbon-nanotubes (CNT), graphene (Gr) and silica (SiO 2 ).…”
Section: Introductionmentioning
confidence: 99%